Strategic corporate covernance: the case of Reykjavík Energy - Steinþórsson, Runólfur Smári; Jónsdóttir, Guðrún Erla; Jónsson, Bjarni Snæbjörn (Research in applied business and economics, 2018)
This article is about strategic corporate governance based on a case study of Reykjavik Energy (OR). OR is a partnership owned by three municipalities. Due to legislative changes requiring electricity production and sales to be operated in a separate company from its distribution, OR was reorganised in 2014 to a parent company and three subsidiaries. At that time OR’s partnership agreement was renewed as well as the ownership strategy and the governance procedures were revised to reflect the new structure. A close look is taken at the processes and practices of strategy and governance that have been developed within OR to ensure that all business units operate in accordance with the ownership strategy. The main findings reveal the practices that enable the board of directors of OR to have the necessary oversight to fulfill its obligations after the reorganization of the company. The study also reveals that the specific conditions after the collapse of the financial system in Iceland in 2008 had an impact on the development of corporate governance within OR. Þessi grein er á sviði stjórnarhátta og fjallar um rannsókn á eigendastefnu og stefnumiðuðum stjórnarháttum hjá Orkuveitu Reykjavíkur (OR). OR er sameignarfyrirtæki í eigu þriggja sveitarfélaga. Staða og þróun OR er áhugaverð vegna lagabreytinga sem knúðu á um að raforkuframleiðsla og -sala skyldi sett í sérstakt fyrirtæki og vera aðskilin frá veiturekstri OR. Í ársbyrjun 2014 var OR skipt upp í samstæðu sem samanstendur af móðurfélagi og þremur dótturfélögum. Við þau tímamót var sameignarsamningur OR endurnýjaður ásamt eigendastefnu, og stjórnarhættir fyrirtækisins endurskoðaðir. Í rannsókninni er fjallað um innra samhengi milli sameignarsamnings OR, eigendastefnu og heildarstefnu fyrirtækisins og rýnt í hvernig unnið er að framkvæmd eigendastefnunnar í samstæðunni. Helstu niðurstöður eru þær að með sérstöku verklagi við rýni, mótun og eftirfylgni er stuðlað að því að stjórn samstæðunnar hafi nauðsynlega yfirsýn til að sinna stefnutengdu hlutverki sínu í ...